Rancang Bangun Kontrol Pemadam Kebakaran Menggunakan Sensor MQ-2 dan Flame Sensor 5 Channel Berbasis Fuzzy Logic - Ardin Fajar Tri Admaja; Edi Kurniawan; Dian Junita Arisusanty (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Fire is an event that often occurs due to human negligence. Losses from fire include damage to goods, business delays and can even cause loss of life. For early handling of fires, a